A comparative evaluation of ChatGPT and human translation of Sundanese cultural terms - Ina Sukaesih; Fanny Puji Rakhmi; Farizka Humolungo; Septina Indrayani; Taufik Eryadi Abdillah (Universitas Syiah Kuala, 2026)
This study addresses a gap in low-resource language translation research by comparing how ChatGPT and a human translator render Sundanese cultural terms into English and evaluating both outputs using established translation quality dimensions. A qualitative descriptive-comparative design was used. A total of 109 cultural terms were extracted from the Sundanese short story Jampe Ngimpi, together with their two English versions (human and ChatGPT). A panel of bilingual Sundanese–English raters familiar with Sundanese culture independently assessed each item for accuracy, acceptability, and readability using Nababan’s Translation Quality Assessment rubric (three-point scale), followed by focus group discussions to reach consensus. The data are analyzed by combining numerical averages with brief qualitative explanations of why certain parts are strong or weak based on the three parameters. The findings show differences in performance across translation quality dimensions. ChatGPT records relatively strong results in accuracy (2.5) and acceptability (2.5), while human translators show a slight advantage in readability (2.6), particularly for terms requiring deeper cultural contextualization. ChatGPT performs better with culturally straightforward items that have clear English equivalents but tends to produce literal calques or transfer Sundanese forms with minimal explanation when faced with culturally specific terms, which can reduce clarity and obscure pragmatic meaning. In contrast, human translators more often apply brief glosses, paraphrasing, and descriptive equivalents that preserve cultural meaning while improving reader comprehension. The results indicate that ChatGPT is effective for initial drafting, while human revision remains essential for ensuring cultural accuracy and contextual appropriateness in Sundanese-English translation.